Comparison of Deep Partial Thickness Burns Wound Healing with Resveratrol Gel and Paraffin Gauze in Wistar Rats: A Case Series - Magdalena, Paulina; Adnyana, I Made Suka; Sanjaya, I Gusti Putu Hendra; Hamid, Agus Roy Rusly Hariantana; Winarti, Ni Wayan (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Various modalities of wound care in burn cases are offered, but there is no standard algorithm used. Paraffin gauze dressing, as one of the commonly used dressings, is considered to have many shortcomings. Resveratrol, a stilbenoid derived from plants, is reported to have a role in wound healing process, it has the potential to be one of the modalities for treating burns. This study aims to strengthen studies on the role of resveratrol in wound healing process, especially in burns compared with paraffin gauze. AIM: This study conducted to prove that resveratrol gel more superior than paraffin gauze in deep partial thickness burns healing process. METHODS: This research is a laboratory experimental study with a post-test only design, simple randomized, and single blind. A sample of 32 Wistar rats with deep partial thickness burns was divided into four control groups and four treatment groups. Control groups were treated using paraffin gauze. Treatment groups were treated using resveratrol gel. Group 1 of each group was assessed for epithelialization. Angiogenesis, fibroblasts, and collagen deposition was assessed on day 5 in Group 2, day 14 in Group 3, and day 21 in Group 4. RESULTS: Angiogenesis was significantly higher in the treatment group than the control group on day 5 and 14 (p = 0.047; 95% CI = 1.23–5.23 and p = 0.032; 95% CI = 0.21–3.28) but not significantly different on day 21 (p = 0.107; 95% CI = −0.43–3.43). The number of fibroblasts in the treatment group was significantly higher on day 5, 14, and 21 (p = 0.004; 0.038; and 0.005; 95% CI = 2.42–17.19; 5.38–16.78; 4.24–15.25). Collagen deposition was not significantly different on day 5 (p = 0.342; 95% CI = −5.65–14.63) but was significantly higher on day 14 and 21 (p = 0.048; 95% CI = 0.11–23.7 and p = 0.002; 95% CI = 10.14–26.57). The epithelialization process occurred earlier in the treatment group than in the control group (p = 0.001). CONCLUSION: Topical administration of resveratrol gel accelerates the epithelialization process, which increases the number of angiogenesis, fibroblasts, and collagen deposition in deep partial thickness burns compared to paraffin gauze.